Light matters: Nest illumination alters egg rejection behavior in a cavity-nesting bird - Canchao Yang; Anders Pape Møller; Wei Liang (Avian Research, 2022)
Egg discrimination by cavity-nesting birds that build nests under dim light conditions was presumed to depend on nest luminance, although this hypothesis has rarely been tested. Tests of egg discrimination ability by cavity-nesting tits under dim light conditions may reveal the selection pressure from brood parasitism that they encounter under natural interactions. We manipulated the intensity of luminance of nests of the Green-backed Tit (Parus monticolus), a potential cuckoo host that possesses a strong discrimination ability of non-mimetic foreign eggs. We performed experiments to test their egg discrimination ability under different light conditions. Our results showed that Green-backed Tits discriminate against non-mimetic foreign eggs under normal light conditions in nest boxes, and this ability persisted at nest luminance as low as 4.78 ​± ​1.31 lux that is several times lower than normal luminance (38.11 ​± ​24.02 lux). However, egg discrimination by Green-backed Tits disappeared when nest luminance was reduced to a minimum of 0.35 ​± ​0.15 lux. The latter value represents total darkness for humans. The present study shows that nest luminance plays a key role in egg discrimination by Green-backed Tits that build nests under dim light conditions. This study provides strong experimental evidence for nest illumination altering egg rejection behavior in cavity-nesting birds.